Disruptive Technology: Saving Money and Inspiring Engagement in Professional Staff. Issue 3 (May 2018) - McPherson, Penne; Talbot, Elizabeth
Abstract : Competent, efficient, and cost-effective delivery of professional development is a challenge in health care. Collaboration of teaching methodologies with academia and acute care offers fresh perspectives and delivery methods that can facilitate optimal outcomes. One multihospital system introduced the academic "flipped classroom" model to its acute care setting and integrated it into professional development requirements. The concept of the flipped classroom requires independent student engagement prior to classroom activities versus the traditional classroom lecture model. Results realized a cost savings in 2 years of $28, 737 in addition to positive employee engagement.